PENGETAHUAN NASABAH DALAM MEMPENGARUHI KEPUTUSAN MENGGUNAKAN PRODUK KREDIT CEPAT AMAN DI PT. PEGADAIAN (PERSERO) SUMBAWA BESAR - Jauhari, Muhammad Irzan; Sutama, I Nyoman (Pusat Riset dan Publikasi, 2024)
This study aims to determine the effect of customer knowledge on customer decisions in using Fast Secured Credit (KCA) products at PT. Pegadaian (Persero) Sumbawa Besar Branch. The type of this study was associative. The type of data used was quantitative obtained directly from primary sources, namely respondents totaling 57 customers. Data collection uses research instruments in the form of questionnaires. The data collection technique used a research instrument in the form of a questionnaire. Data analysis was carried out using simple linear regression analysis techniques, partial hypothesis testing (t test), and determinant coefficient testing (R2). The results of this study showed that the customer knowledge had a positive and significant effect on customer decisions in using Fast Secured Credit (KCA) products at PT. Pegadaian (Persero) Sumbawa Besar Branch. The ability of customer knowledge variables on customer decision variables in using KCA products at PT. Pegadaian (Persero) Sumbawa Besar Branch was 7.6%, while the remaining of 92.4% was affected by other variables outside this research model, such as marketing mix factors and socio-cultural environmental factors.